Effect of cholecystectomy on bile acid diarrhoea biomarkers: A prospective clinical study. Issue 5 (6th September 2021) - Borup, Christian; Hedbäck, Nora; Wildt, Signe; Rumessen, Jüri J.; Bouchelouche, Pierre; Gauliard, Emilie; Rainteau, Dominique; Munck, Lars K.
Summary: Background: The pathophysiological mechanisms of bile acid diarrhoea after cholecystectomy are unknown. Therefore, we aimed to explore the effects of cholecystectomy on the plasma biomarkers of bile acid diarrhoea: fibroblast growth factor 19 and 7α‐hydroxy‐4‐cholesten‐3‐one. Methods: Patients were examined prospectively before and after cholecystectomy. Diary registration of bowel habits with the Bristol stool scale was done for 7 days before each visit. Blood was collected at fasting and after ingestion of a solid study meal with 1250 mg unconjugated chenodeoxycholic acid. Plasma fibroblast growth factor 19 was measured with enzyme‐linked immunosorbent assay and the complete bile acid profile including 7α‐hydroxy‐4‐cholesten‐3‐one with high‐performance liquid chromatography–tandem mass spectrometry. Results: Eighteen patients completed the study. The median postoperative follow‐up time was 4.6 months (interquartile range [IQR] 3.9‐5.8). Diary‐registered bowel movement frequency and stool consistency were unchanged; none developed diarrhoea. Before cholecystectomy, mean fibroblast growth factor 19 was 102 pg/mL (95% CI 74‐141) vs 92 pg/mL (67‐125) after ( P  = .29; paired t test). Following the meal, the median 150‐minute increment from fasting in fibroblast growth factor 19 was 81 pg/mL (IQR: −20 to 274) before and 186 pg/mL (111‐382) after cholecystectomy ( P  = .03; Wilcoxon‐test). Mean fasting 7α‐hydroxy‐4‐cholesten‐3‐one was unchanged 6.0 ng/mL (4.1‐8.7) vs 7.5 ng/mL (5.5‐10.0) ( P  = .63; paired t test). Conclusions: The stimulated postprandial response in fibroblast growth factor 19 increased after cholecystectomy, whereas fasting plasma biomarkers and bowel habits did not change significantly 3‐6 months after cholecystectomy. ClinicalTrials.gov: NCT03168555.